PENGARUH PROFITABILITAS, LEVERAGE, LIKUIDITAS DAN UKURAN PERUSAHAAN TERHADAP NILAI PERUSAHAAN - Rizky Adhitya Nugraha; Mohammad Fany Alfarisi (STIE AMKOP, 2020)
This research is conducted to know the effect of profitability, Leverage, liquidity and size of the company against the value of companies in manufacturing companies Listing on the Indonesia Stock Exchange (IDX) period 2014 – 2018. To determine the samples in this study use the Purposive sampling criteria on the IDX-listed manufacturing companies. The type of data used in this study is secondary data, the company's annual report. In the software research used is Eviews software. This research shows results, where profitability has a positive and significant influence on the value of the company. Leverage has a positive and significant influence on the company's value. Liquidity has a positive and insignificant influence on the value of the company. The company's size has a negative and insignificant influence on the company's value. Keywords: Profitability, Leverage, Liquidity, Company Size